Impact of Maternal Food Restriction on Heart Proteome in Appropriately Grown and Growth-Restricted Wistar—Rat Offspring - Zouridis, Andreas (Nutrients, 2021)
Objective: Fetal growth restriction is associated with increased postnatal cardiovascular morbidity. The alterations in heart physiology and structure caused by in utero nutrient deprivation have not been extensively studied. We aim to investigate the impact of maternal food restriction on the cardiac proteome of newborn rats with normal (non-fetal growth-restricted (FGR)) and reduced (FGR) birth weight. Methods: On day 14 of gestation, 10 timed pregnant rats were randomized into two nutritional groups: (a) Standard laboratory diet and (b) 50% global food restriction. Pups born to food-restricted mothers were subdivided, based on birthweight, into fetal growth-restricted (FGR) and non-FGR, while pups born from normally nourished mothers were considered controls. Rat neonates were euthanized immediately after birth and the hearts of 11 randomly selected male offspring (n = 4 FGR, n = 4 non-FGR, n = 3 control group) were analyzed using quantitative proteomics. Results: In total, 7422 proteins were quantified (q < 0.05). Of these, 1175 were differentially expressed in FGR and 231 in non-FGR offspring vs. control with 151 common differentially expressed proteins (DEPs) between the two groups. Bioinformatics analysis of DEPs in FGR vs. control showed decreased integrin and apelin cardiac fibroblast signaling, decreased muscle contraction and glycolysis, and over-representation of a protein network related to embryonic development, and cell death and survival. Conclusion: Our study illustrates the distinct proteomic profile of FGR and non-FGR offspring of food-restricted dams underlying the importance of both prenatal adversities and birth weight in cardiac physiology and development.